1999
DOI: 10.1038/45568
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a potassium-selective prokaryotic glutamate receptor

Abstract: Ion channels are molecular pores that facilitate the passage of ions across cell membranes and participate in a range of biological processes, from excitatory signal transmission in the mammalian nervous system to the modulation of swimming behaviour in the protozoan Paramecium. Two particularly important families of ion channels are ionotropic glutamate receptors (GluRs) and potassium channels. GluRs are permeable to Na+, K+ and Ca2+, are gated by glutamate, and have previously been found only in eukaryotes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
266
0
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(285 citation statements)
references
References 27 publications
14
266
0
5
Order By: Relevance
“…However, the presence of rapid desensitization in the ⌬402 channels together with removal of desensitization by cyclothiazide of show that the N-terminal domain is not an obligatory participant in these processes. This is also consistent with a recent model for AMPA receptor desensitization, inspired and supported by high resolution structures of S1S2-ligand complexes, proposing that destabilization of a dimer interface between agonist-binding domains of neighboring subunits may underlie desensitization (23,30,31).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, the presence of rapid desensitization in the ⌬402 channels together with removal of desensitization by cyclothiazide of show that the N-terminal domain is not an obligatory participant in these processes. This is also consistent with a recent model for AMPA receptor desensitization, inspired and supported by high resolution structures of S1S2-ligand complexes, proposing that destabilization of a dimer interface between agonist-binding domains of neighboring subunits may underlie desensitization (23,30,31).…”
Section: Discussionsupporting
confidence: 76%
“…C, the AMPA receptor antagonist CNQX blocks the current elicited by 1 mM glutamate in cells expressing ⌬402. units and has no X domain, demonstrates that a direct coupling between the ligand-binding S1-S2 domain and the ion channel gate can take place without an obligatory involvement of an N-terminal domain (23). The overall sequence similarity between the prokaryotic channel and eukaryotic iGluR is fairly low, however, and even the ligand binding mechanism employed by GluR0 seems to profoundly differ that observed for the AMPA receptor (24).…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the prokaryotic GluR0, which lacks the ATD, the M4 segment, as well as the CTD, and is presumably more ancient than mammalian iGluRs, exhibit slow gating kinetics (51). We therefore speculate that the emergence of the ATD, the M4, and the CTD later in evolution conferred additional efficiency to receptor tetramerization, thus allowing the LBD to evolve structural features required for fast gating.…”
Section: Discussionmentioning
confidence: 99%
“…The iGluRs internally contain ligandgated ion channels. Chen et al (16) have identified an iGluR, GluR0, from a prokaryote, the cyanobacterium Synechocystis. GluR0 has a hybrid structure between iGluRs and potassium channels and is thought to be a common ancestor for these molecular families.…”
Section: Discussionmentioning
confidence: 99%